PEMBERDAYAAN MASYARAKAT DALAM MELESTARIKAN KULINER KUE TRADISIONAL PADAMARAN KHAS SEBERANG KOTA JAMBI BERBASIS KEARIFAN LOKAL - Machfia Win Hidayati; Syafrudin; Fatniaton Adawiyah; Rukmiyati (CV. Lafadz Jaya, 2025)
Write a brief suTraditional culinary heritage is an important component of local culture and economic potential for communities. One of the traditional foods originating from Seberang Kota Jambi is Padamaran cake, which has distinctive taste, texture, and cultural value. However, modernization and changing consumption patterns pose challenges to the sustainability of traditional culinary products. This community service activity aimed to empower local communities in preserving and developing Padamaran traditional cake through training and mentoring programs. The methods used in this activity included socialization, training, mentoring, and evaluation. The program was conducted in Ulu Gedong Village, Danau Teluk District, Jambi City, involving local culinary entrepreneurs and community members. The results showed that participants gained better understanding of the importance of preserving traditional culinary heritage as well as improving their knowledge in product innovation, packaging, and marketing strategies. Participants also developed awareness about market segmentation and promotion strategies using both offline and online platforms. This activity demonstrates that community empowerment through training and mentoring can contribute to preserving local culinary traditions while enhancing economic opportunities for local communities. Further programs are recommended to strengthen business management and marketing capabilities to ensure the sustainability of traditional culinary businesses.